Answer:
A. 3√3/4
Step-by-step explanation:
√27x / √48 = (√9 * √3 *√x) / (√16 * √3) = (3 * √3 *√x) / (4 * √3)
divided √3 both side
= 3√x / 4
1000 x 5 = 5000
Lana's dad would take about 5000 steps.
5000 x 2 = 10,000
Lana would take about 10,000 steps.
Glad I could help, and good luck!
Answer:
and ![4x-3y=-2](https://tex.z-dn.net/?f=4x-3y%3D-2)
Step-by-step explanation:
The asymptote equation of a translate hyperbola with equation
is ![y=\pm\frac{b}{a}(x-h)+k](https://tex.z-dn.net/?f=y%3D%5Cpm%5Cfrac%7Bb%7D%7Ba%7D%28x-h%29%2Bk)
The given hyperbola has equation: ![\frac{(x-1)^2}{36}-\frac{(y-2)^2}{64}=1](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-1%29%5E2%7D%7B36%7D-%5Cfrac%7B%28y-2%29%5E2%7D%7B64%7D%3D1)
Or ![\frac{(x-1)^2}{6^2}-\frac{(y-2)^2}{8^2}=1](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-1%29%5E2%7D%7B6%5E2%7D-%5Cfrac%7B%28y-2%29%5E2%7D%7B8%5E2%7D%3D1)
Comparing to ![\frac{(x-h)^2}{a^2}-\frac{(y-k)^2}{b^2}=1](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-h%29%5E2%7D%7Ba%5E2%7D-%5Cfrac%7B%28y-k%29%5E2%7D%7Bb%5E2%7D%3D1)
We have a=6 and b=8, h=1 and k=2.
We substitute this values to get:
![y=\pm\frac{6}{8}(x-1)+2](https://tex.z-dn.net/?f=y%3D%5Cpm%5Cfrac%7B6%7D%7B8%7D%28x-1%29%2B2)
![y=\pm\frac{4}{3}(x-1)+2](https://tex.z-dn.net/?f=y%3D%5Cpm%5Cfrac%7B4%7D%7B3%7D%28x-1%29%2B2)
![3y=\pm4(x-1)+6](https://tex.z-dn.net/?f=3y%3D%5Cpm4%28x-1%29%2B6)
We split the plus or minus sign to get:
![3y=4x-4+6](https://tex.z-dn.net/?f=3y%3D4x-4%2B6)
![3y=4x+2](https://tex.z-dn.net/?f=3y%3D4x%2B2)
![3y-4x=2](https://tex.z-dn.net/?f=3y-4x%3D2)
Or
![3y=-4(x-1)+6](https://tex.z-dn.net/?f=3y%3D-4%28x-1%29%2B6)
![3y=-4x+4+6](https://tex.z-dn.net/?f=3y%3D-4x%2B4%2B6)
![3y+4x=10](https://tex.z-dn.net/?f=3y%2B4x%3D10)
Answer:
15 ft 1 inch
Step-by-step explanation:
We are asked to calculate the total length of a walkway given that three boards are joined together and these boards have the lengths given in the question.
To calculate the total length of the walkway, we simply add the lengths of the individual boards to one another. This is given as follows:
5ft 10 inches + 5ft 7 inches + 3ft 8 inches = 13ft 25 inches
Now, basic conversions is that 1 ft is 12 inches. Hence from 25 inches, we can get 2ft 1 inch
Thus we can modify our 13ft 25 inches to be 15ft 1 inch